KELAS-KELAS BCI-ALJABAR DAN HUBUNGANNYA SATU DENGAN YANG LAIN - ., Winarsih; ., Suryoto (MATEMATIKA, 2014)
Several classes of BCI-algebras as the class of weakly implicative BCI-algebras, BCK-algebras, medial BCI-algebras, branchwise implicative BCI-algebras and branchwise commutative BCI-algebras have relation one another. A branchwise implicative BCI-algebras is a class of BCI-algebras which to fulfill condition of branchwise implicative. By using characters of the class of BCK-algebras and element of the class of medial BCI-algebras, we investigate relations between branchwise implicative BCI-algebras exist with others classes of the class of BCI-algebras as the class of weakly implicative BCI-algebras and branchwise commutative BCI-algebras.